تحليل إدارة المخاطر الائتمانية في المصارف الإسلامية دراسة تطبيقية على مجموعة البركة المصرفية - فضلية, عابد; مملوك, أنس (Latakia University Journal - Economic and Legal Sciences Series, 2015)
يهدف البحث إلى تحليل قضية أساسية تتعلق بإدارة المخاطر الائتمانية في المصارف الإسلامية من خلال تحليل إدارة المخاطر في المصرف الإسلامي, وأنواع ومخاطر صيغ التمويل الإسلامي والأساليب المتبعة لمواجهة تلك المخاطر والتحديات التي تواجه المصارف الإسلامية. وتكمن مشكلة البحث من حيث أن النشاط الائتماني يعتبر من احد أهم الوظائف الرئيسية التي تقدمها المصارف وهي من أكثر الانشطه ربحيه وأكثرها خطورة، حيث تنشأ مخاطر الائتمان نتيجة عدم قدرة المدينين على الوفاء بالتزاماتهم في مواعيد الاستحقاق، وما يترتب على ذلك من خسائر يتحملها المصرف، لذلك ويقوم هذا البحث على فرضية أساسية تتعلق بتحليل إدارة مخاطر الائتمانية في المصارف الإسلامية, للمحافظة على مستويات ائتمانية متدنية المخاطر. ويخلص البحث إلى أن مخاطر صيغ التمويل الإسلامي تأتي في مقدمة المخاطر التي تتعرض لها المصارف الإسلامية, لذلك فإن تفعيل دور إدارة المخاطر في البنوك الإسلامية تمكنها من فهم وتحديد وقياس ومعالجة المخاطر المختلفة، وتقليلها إلى أدنى حد ممكن. The research aims to analyse the key issue relating to the management of credit risk in Islamic Banks through the analysis of risk management in the Islamic Bank, the types and formats of Islamic finance risks, the methods used to address those risks and challenges faced by Islamic banks. The problem with the research terms seems that credit activity is one of the most single important key functions offered by the banks, one of the activities profitable and most dangerous, where credit risk arises as a result of the inability of the debtors to meet their obligations in the dates of maturity, and the consequent loss incurred by the bank, and therefore. It is based on the premise of basic research related to the analysis of credit risk management in Islamic banks, to maintain low levels of credit risk. The study concludes that the risk of Islamic modes of financing in the forefront of the risks faced by Islamic banks, so that the activation of the role of risk management in Islamic banks to enable them to understand and identify, measure and address the various risks, and minimize possible.